2017
DOI: 10.3390/molecules22111843
|View full text |Cite
|
Sign up to set email alerts
|

Thymosin α1 Interacts with Hyaluronic Acid Electrostatically by Its Terminal Sequence LKEKK

Abstract: Thymosin α1 (Tα1), is a peptidic hormone, whose immune regulatory properties have been demonstrated both in vitro and in vivo and approved in different countries for treatment of several viral infections and cancers. Tα1 assumes a conformation in negative membranes upon insertion into the phosphatidylserine exposure as found in several pathologies and in apoptosis. These findings are in agreement with the pleiotropy of Tα1, which targets both normal and tumor cells, interacting with multiple cellular component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 87 publications
(139 reference statements)
0
11
0
Order By: Relevance
“…Studies have shown that the second binding site plays a major role in binding. Studies on Tα1 indicated that the binding is mainly related to its terminal L 16 KEKK 20 ( Mandaliti et al, 2017 ). The combination of HA and these two substances occurred mainly through electrostatic forces, which was different from the role of HA with TSG-6 and CD44.…”
Section: Hyaluronic Acidmentioning
confidence: 99%
“…Studies have shown that the second binding site plays a major role in binding. Studies on Tα1 indicated that the binding is mainly related to its terminal L 16 KEKK 20 ( Mandaliti et al, 2017 ). The combination of HA and these two substances occurred mainly through electrostatic forces, which was different from the role of HA with TSG-6 and CD44.…”
Section: Hyaluronic Acidmentioning
confidence: 99%
“…Tα1 was also recently proven to interact with hyaluronic acid (HA) by its C-terminal sequence LKEKK 28 . Tα1 shares the similar sequences with CD44 and RHAMM which both can bind with HA.…”
Section: Discussionmentioning
confidence: 99%
“…Although use of waterLOGSY in studies of protein-glycan interactions is common, an example involving GAG has been published only recently. Interestingly, in that study, Mandaliti et al did not use the experiment to probe the ligand, but to identify protein residues that are involved in hyaluronan binding [ 33 ], providing a good demonstration of the versatility of the experiment. Although information from waterLOGSY is limited to hydration, it can often be used to create more accurate models and provide a deeper understanding of the energetics of binding.…”
Section: Common Nmr Experimentsmentioning
confidence: 99%